Meaning-making in multimodal spaces: the role of YouTube in promoting organic farming practices in Indonesia - Sarwoprasodjo, Sarwititi; Mardiansyah, Iis; Susanto, Tri; Flor, Alexander G.; Lubis, Djuara P. (Frontiers in Communication, 2025)
IntroductionDigital platforms are transforming agricultural education in developing countries, yet their role in promoting sustainable farming practices remains understudied. This study investigates how YouTube facilitates knowledge transfer and behavioral change in Indonesian organic farming communities.MethodsA mixed-methods design was employed, analyzing 1,391 viewer comments from three popular composting tutorial channels. Quantitative content analysis identified engagement patterns, while qualitative analysis explored meaning-making processes. The study also examined multimodal features of videos to understand how linguistic, visual, and audio strategies shaped pedagogical identities.ResultsThree distinct pedagogical identities were identified: the Scientific Demonstrator (technical precision with accessibility), the Faith-Based Pragmatist (religious framing with practical guidance), and the Community Motivator (collective storytelling with emotional support). Statistical analysis showed significant variations in viewer engagement (χ2 = 23.06, p < 0.001), with faith-based approaches producing the highest reports of behavioral change (26%). Qualitative analysis revealed six interconnected meaning-making processes— acceptance, transformation, restoration, appreciation, enactment, and identity reconstruction. The Indonesian concept of balas budi (reciprocal obligation) emerged as a cultural factor influencing participation.DiscussionFindings demonstrate that effective digital agricultural education requires pedagogical plurality rather than standardization. YouTube can catalyze sustainable agricultural transitions when content aligns with local cultural values and addresses psychological barriers to adoption. This study highlights YouTube’s potential as a scalable model for digital agricultural extension services in Southeast Asia.